Mutual aid for the arts in nineteenth- and twentieth-century Milan: The 'Pio Istituto Teatrale'. (November 2020) - Pierotti, Mariarita; Capocchi, Alessandro; Orlandini, Paola
In the nineteenth century, when the theatre arts were at their peak, Milan was considered the intellectual and artistic capital of Italy. This article explores the objectives and the functioning of an important mutual aid company based in Milan – the Pio Istituto Teatrale – through its accounting system. These accounting documents clearly convey the dual nature of this organization, which was dedicated to protecting both social welfare and the arts. This study confirms the social role of accounting and its implications. In recent years, the attention paid to accounting in artistic institutions has been increasing. However, while many studies have explored Italian mutual aid societies in general, few have considered those in the artistic field specifically. This article attempts to rectify this oversight by examining a mutual aid society functioning in the world of theatre via its accounting records.